POLYCARB UZ - STUDYING THE EFFECT OF THE DRUG ON THE GROWTH AND DEVELOPMENT OF CALVES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The effect of Polycarb on the growth and development of calves in Beshbola farm of Pastdargom district of Samarkand region was determined.